Una mirada arqueológica al complejo religioso Nuestra Señora de la Merced en Santiago de Cali. (2024)
Heritage encompasses more than individual or group material assets; includes a common and collective heritage built by a society throughout its history. This heritage includes spiritual, material, immaterial, intellectual and emotional manifestations that define its identity. Within this heritage is the Immovable Cultural Heritage, which reflects the history and events that shape a society.